Improvement of agrobiomass quality and lovastatin production for inhibition of methanogenesis by Aspergillus terreus - Jahromi, Mohammad Faseleh (2012)
Methane (CH4) is a greenhouse gas with 23 to 25 times greater warming effect than carbon dioxide on the ecosystem. Agricultural activities contributes 40% of total anthropogenic source of CH4 with 15 to 20% produced by enteric fermentation from ruminant animals. At the same time, huge quantities of agricultural byproducts are produced annually and because of their high fiber content, these byproducts are of limited use as animal feed. The objective of this thesis was to elucidate the use of Aspergillus terreus as a biological agent to mitigate methanogens activity. The potential of two strains of A. terreus (ATCC 20542 and ATCC 74135) to produce lovastatin in solid state fermentation (SSF) using rice straw (RS) and oil palm frond (OPF) as substrates was investigated. Results of this study showed that RS was a better substrate than OPF for lovastatin production (with maximum production of 157.07 mg/kg DM using A. terreus ATCC 74135) and reduction of cellulose and hemicellulose content. In a follow-up study, different factors (moisture, temperature, amount of inoculum, pH and incubation time) known to affect SSF process were optimized for lovastatin production by both strains of A. Terreus using RS as substrate. A combination of 25°C incubation temperature, 10% inoculum size, pH 6, 50% initial moisture content and 8 days fermentation time provide the best condition for lovastatin production with the maximum yield of 260.85 mg lovastatin/kg DM. The ability of A. terreus (ATCC 74135) to produce cellulolytic enzymes and to reduce lignocelluloses content of RS in SSF using the optimized condition obtained in the previous experiment was investigated in Chapter 4. Results of the study suggested that 8 days fermentation was suitable for production of the required cellulolytic enzymes. Fungal treatment significantly reduced neutral detergent fiber (NDF), acid detergent fiber (ADF), cellulose and hemicelluloses contents of RS by 19.96, 13.8, 16.32 and 32.87%, respectively, and resulted in significant increase in content of reducing sugar in the treated RS. Lovastatin is an inhibitor of HMG-CoA reductase, a key enzyme responsible for the production of isoprenoid which is a component of the membrane in Archaeal cell, thus lovastatin can be used as an anti-methanogenesis agent. Effect of pure lovastatin and fermented rice straw extract (FRSE) containing lovastatin on pure culture of methanogenic Archaea (Methanobrevibacter smithii) was investigated in the third experiment (Chapter 5). Results of this experiment showed that both treatments significantly reduced the growth (optical density of 0.390 for control, 0.065 for 50 μg/ml lovastatin and 0.031 for 500 μg/ml FRSE), CH4 production (8.67%, 0.31% and 0% for control, 50 μg/ml lovastatin and 500 μg/ml FRSE treatments, respectively) and methanogenesis activity of M. smithii. However, lovastatin in the FRSE which primarily made up of the more active hydroxyl form, recorded stronger suppression on the growth of M. smithii and CH4 production. Both treatments (pure lovastatin and FRSE) significantly increased the expression of HMG-CoA reductase gene in M. smithii (6.92 and 9 fold increased in 10 μg/ml lovastatin and 100 μg/ml FRSE treatments, respectively). Transmission Electron macrographs showed that lovastatin distorted the morphological structure in M. smithii which could be due to the inhibition of isoprenoid production that is involve in the phospholipids formation in the cell membrane of this microorganism. In the final experiment (Chapter 6), in-vitro gas production technique was used to study the effect of fungal treated RS containing lovastatin on mixed culture of rumen microbiota. Fermented rice straw (FRS) significantly reduced total gas (from 55.9 mL for control to 47.0 mL for FRS) and CH4 productions (from 281.148 μM for control to 47.0 μM for FRS), ratios of CH4:gas (from 0.113 for control to 0.102 for FRS), gas:VFA (from 0.965 for control to 0.862 for FRS) and CH4:VFA (from 0.054 for control to 0.044 for FRS). In-vitro dry matter digestibility of FRS (49.01%) was significantly higher than that for the untreated RS (45.81%). The population of total methanogenic bacteria and fungi in the FRS treatments was significantly lower than those in the control but population of Ruminococcus albus (cellulolytic bacteria) increased significantly in the FRS treatments. Results of this thesis showed that lovastatin can be produced from agro-biomass such as RS using A. terreus ATCC 74135 in SSF. Besides reducing the fiber content of RS which resulted in higher nutrients digestibility, the FRS also contain higher protein content (due to increased fungal cell-mass) and cellulolytic enzymes which may continue to be active in the rumen of host animals. In addition, lovastatin in the FRS can effectively reduce methanogenesis, primarily through the inhibition of HMG-CoA reductase in methanogenic Archaea. Results of this thesis also showed that efficiency of methanogenesis inhibition by the FRS is higher than pure lovastatin due to the higher quantity of the more active hydroxyl form of lovastatin in the FRS. It can be concluded that fermentation of rice straw using A. terreus, is applicable method for enhancing the quality of this agro-biomass as ruminant feed and reduction of ruminal methane production.